(untitled) - Ng, Yew-Kwang (New York, 2003)
This volume is a collection of selected papers using the framework of inframarginal analysis of the division of labour held at Monash University on 6-7 July 2001. This framework, pioneered mainly by Professor Xiaokai Yang, (with joint researches involving all the three editors and many of the authors), has been recommended by Professor James Buchanan (Nobel Laureate in Economics) as the most important analysis in economics in the world today.
Keywords: Electronic commerce